2018
DOI: 10.9778/cmajo.20170161
|View full text |Cite
|
Sign up to set email alerts
|

Cancer drug expenditure in British Columbia and Saskatchewan: a trend analysis

Abstract: Background: Expenditure on systemic therapy for cancer has been increasing quickly owing to population growth, increased use, both in the number of users and in prescription volume, and rising drug prices. Our objective was to describe trends in expenditure in British Columbia and Saskatchewan's cancer care systems and to elucidate these drivers of growth. Methods:In this trend analysis, we obtained pharmacy dispensing records from the BC Cancer and Saskatchewan Cancer Agency pharmacies for all anticancer ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In 2018, the average health expenditure related to cancer care per patient was EUR 195, and the average cancer drug spending per patient was EUR 61 ( 12 ). Another study in Canada identified the growth factors related to overall cancer drug expenditures ( 11 ). In the US, cancer treatment accounts for USD 60.9 billion of direct medical costs and USD 15.5 billion of indirect morbidity costs based on data that ranged from 1998 to 2000 ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the average health expenditure related to cancer care per patient was EUR 195, and the average cancer drug spending per patient was EUR 61 ( 12 ). Another study in Canada identified the growth factors related to overall cancer drug expenditures ( 11 ). In the US, cancer treatment accounts for USD 60.9 billion of direct medical costs and USD 15.5 billion of indirect morbidity costs based on data that ranged from 1998 to 2000 ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have estimated trends associated with expenditures related to cancer care and cancer drugs (10)(11)(12); however, there have been few studies examining the magnitude of cancer care utilization and spending related to anti-cancer therapy. In Korea, several studies have analyzed cancer incidence, survival, prevalence, and mortality using the National Cancer Incidence Database (6,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), but few of these studies examined trends related to anti-cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These new treatment options have also substantially increased the demand on outpatient oncology services and oncology infusion units. [5][6][7][8] However, these increases and the relative effects on provider clinic visits (CVs), oncology infusion (OI) visits and oncology prescriptions (OPs) have not been quantitatively measured. An improved understanding of the requirements to introduce novel systemic treatments is needed to allow better planning of clinic and infusion space and staffing of oncologists, nurses and pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…In related research, Pataky and colleagues model strategies for the elimination of cervical cancer in British Columbia and find that the greatest gains would come from increasing self-sampling uptake among underscreened populations. 1 Increasing uptake in hard-to-reach populations could be achieved by reducing barriers to accessing self-testing, or self-sampling. Guidelines from the World Health Organization published in 2022 recommend that self-sampling for human papillomavirus (HPV) be included in cervical cancer screening.…”
mentioning
confidence: 99%